Size Structure, Long-Weight Relations And Growth Angel Ornamental Fish (Pomacanthus Imperator) In Spermonde Waters, South Sulawesi, Indonesia - Sulkifli, Sulkifli; Mauli Kasmi; Yusri Muhammad Yusuf (International Journal of Technology and Education Research, 2023)
Angel Ornamental Fish (Pomacanthus imperator) is species most expensive from group fish angelfish and has a higher bargaining value than other types of ornamental fish, making it a target fish for fishermen fish ornamental. Production fish This Still depends from arrest in natural because cultivation Not yet successfully developed, so there is a possibility that this species is experiencing overfishing. The purpose of this research is to know the status of the candidate parent, structure size, growth Angelfish (Pomacanthus imperator) in waters spermmonde South Sulawesi. The research method is based on parallel sampling in the waters of the Spermonde Islands from April to November 2022 with using the dependent survey method with sampling techniques, interviews, observation, and documentation. Absolute age and growth of angelfish determined with analysis plot Gulland and Holt. Results study show that mode long total fish angelfish in Fisheries spermmonde (9.5-11.5 cm) relatively many and is a group fish mature. The relationship between length and weight is allometric, the growth pattern is 0.4934 cm/ year with a maximum length 41.7 cm at the age of 10 years and the majority are adult fish or adult groups.